Evaluasi Muka Air Cakung Drain Hilir terhadap Hujan Maksimum 2013 dan 2014 - Puji Harsanto; Muhammad Arif Banjaran Sari; Surya Budi Lesmana (Universitas Muhammadiyah Yogyakarta, 2014)
Cakung floodway is a drainage channel that plays an importance rule for the overall of drainage system in Jakarta. Rainfall in 2013 and 2014 produced a big flood in Jakarta. Based on flood map Jakarta 2013 and 2014, there are inundated areas due to 2013’s and 2014’s rainfall. So, it is necessary to analyze the flood water level in channel floodway. Using HEC-RAS, this study aimed to evaluate the water level due to the maximum rainfall in 2013 and 2014. HEC-RAS is a tool for 1D hydraulic modeling and has reliability in routing of canal water level or river flooding. The results show that the maximum rainfall in 2013 provides a significant increasing of water level in Cakung floodway compared with the maximum rainfall in 2014. Soon, the need for canal normalization to reduce flood water level in Cakung floodway should be considered.